Republic of Kazakhstan : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report, 2002)
This Selected Issues paper presents a brief overview of developments and prospects for the petroleum sector of the Republic of Kazakhstan. The paper conducts a comprehensive assessment of fiscal vulnerability, fiscal sustainability, and fiscal stance in Kazakhstan, focusing on the government's non-oil budget balance while taking into account some of the key characteristics of resource-rich countries. The paper states that the key issue is how much the government should consume and save out of oil revenues and how these decisions should change in response to changes in key aspects of fiscal vulnerability in Kazakhstan.